Association Between Depression, Anxiety, and Antidepressant Use With T-Wave Amplitude and QT-Interval - Hu, Mandy X.; Lamers, Femke; Penninx, Brenda W. J. H.; de Geus, Eco J. C. (Frontiers in Neuroscience, 2018)
Objectives: Cardiac repolarization may be affected by psychiatric disorders and/or antidepressant use, but evidence for this is inconclusive. This study examined the relationship between depressive and anxiety disorder and use of antidepressants with T-wave amplitude (TWA) and QT-interval. Methods: Data was obtained from the Netherlands Study of Depression and Anxiety (n=1383). Depression/anxiety was diagnosed with the DSM-IV based Composite International Diagnostic Interview. The use of tricyclic antidepressants (TCAs), selective serotonin and noradrenalin reuptake inhibitors (SNRIs), and selective serotonin reuptake inhibitors (SSRIs) was established. T-wave amplitude and QT-interval corrected for heart rate (QTc) were obtained from an ECG measured in a type II axis configuration. Results: Compared to controls, persons with depression or anxiety disorders did not show a significantly different TWA (p = .58; Cohen’s d = 0.046) or QTc (p = .48; Cohen’s d = -0.057). In spite of known sympathomimetic effects, TCA use (p = .26; Cohen’s d = -.162) and SNRI use (p = .70; Cohen’s d = -0.055) were not significantly associated with a lower TWA. TCA use (p = .12; Cohen’s d = 0.225) and SNRI use (p = .11; Cohen’s d = 0.227) were also not significantly associated with a prolonged QTc. Conclusion: We did not find evidence that either depressive/anxiety disorder or antidepressant use is associated with abnormalities in TWA or QTc. Earlier found sympathomimetic effects of TCAs and SNRIs are not evident in these measures of cardiac repolarization.